EDUCA – COMPUTATIONAL ENVIRONMENT FOR DESIGN AND SHARING OF THE ACESSIBLE EDUCATIONAL MATERIALS - Santos, Cristina Paludo; Ellwanger, Cristiane; Losekann, Maikel (Human Factors in Design, 2013)
<!–[if gte mso 9]> <![endif]–> This paper describe the main characteristics of the EducA – an environment to support of the design, management and sharing of the accessible pedagogical materials. The EducA provides resources adaptability and adaptively interface to maximize the user interaction process with the environment. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>